2015
DOI: 10.3892/mmr.2015.4547
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of the Tougu Xiaotong capsule on morphology and osteoprotegerin/nuclear factor-κB ligand expression in rabbits with knee osteoarthritis

Abstract: Abstract. The imbalance of subchondral bone remodeling is a common pathological feature in the progression of osteoarthritis. In the current study, using a rabbit model of knee osteoarthritis, the effects of the Tougu Xiaotong capsule (TGXTC) on the cartilage and subchondral bone were investigated. In addition, osteoprotegerin (OPG), an inducer of bone formation, and receptor activator of nuclear factor-κB ligand (RANKL), a regulator of bone resorption in the subchondral bone, were assessed, in order to furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…To this end, the literature suggests that in addition to cartilage, other articular tissues, including the subchondral bone, should be targeted. Previous findings have shown that TGXTC has therapeutic effects on knee OA (25) through multiple targets (22,23,(25)(26)(27). In this study, we investigated the effect of TGXTC on subchondral bone and its relevant mechanisms of inflammatory factors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To this end, the literature suggests that in addition to cartilage, other articular tissues, including the subchondral bone, should be targeted. Previous findings have shown that TGXTC has therapeutic effects on knee OA (25) through multiple targets (22,23,(25)(26)(27). In this study, we investigated the effect of TGXTC on subchondral bone and its relevant mechanisms of inflammatory factors.…”
Section: Discussionmentioning
confidence: 98%
“…Tougu Xiaotong capsule (TGXTC) is an effective prescription in OA treatment which consists of Ligusticum chuanxiong, Morinda officinalis, Sarcandra glabra and Paeonia lactiflora (22,23). There are many effective molecules in TGXTC, which is multi-drug, multi-path and multi-target of molecular mechanism for the treatment of OA, and the non-linear regulation pattern exists in TGXTC ligand-target interaction network (24).…”
Section: Introductionmentioning
confidence: 99%
“…After BMD and BMC of the rabbit femoral head were determined, it was found that the bone mass in the OP+OA group was signi cantly reduced, and the cartilage destruction was severe, In this experiment, an experimental animal model was established by castration method combined with Hulth'S method. Rabbits were driven to walk for 30 minutes one week after modeling, which was equivalent to the middle and late stages of OA at 4 weeks [11]. Compared with the normal group, the Pelletier-JP and Minkin's scores of the joints in the OP+OA group and the OA group were signi cantly higher, indicating that the severity of the lesion is proportional to the score, and also indicating the success of this experiment.…”
Section: Discussionmentioning
confidence: 98%
“…When there is an increase in RANKL/OPG ratio there is predominance of bone destruction, and when there is a decrease of this index, there is protection of subchondral bones. [11404142] In OA, various interleukins and cytokines such as IL-1β, IL-6, IL-11, IL-17, and TNF-α lead to increased formation of RANKL and decreased production of OPG resulting in bone lost. [38394041]…”
Section: Pathophysiology Of Osteoarthritismentioning
confidence: 99%